HIKMAH PENURUNAN AL-QUR'AN SECARA BERANGSUR - Maulana Dwi Kurniasih; Dyah Ayu Lestari; Ahmad Fauzi (Mimbar Agama Budaya, 2020)
Abstract. The verses of the Qur’an are not revealed as a whole at once, but gradually. The letters he sent were not the same in length and in short, sometimes they were sent in full and sometimes only in part. Through the study of literature, the article concludes that the gradual revelation of the Qur'an a lot of wisdom that will be obtained that is to set the heart of the Prophet, weaken his opponents, easy to understand and memorize, the arrangement will be in accordance with traffic events. The gradual revelation of the verses of the Qur’an gives some wisdom among them: strengthening the heart of the Prophet Muhammad SAW; Easy to memorize and understand; the believers are enthusiastic in accepting the Qur’an and actively practicing it; Accompanying events in society and gradually in establishing a law; weakening his opponents (miracles), and challenging the disbelievers who deny the Qur’an. Abstrak.  Ayat-ayat al-Qur’an tidaklah diturunkan keseluruhan sekaligus secara, tetapi secara berangsur-angsur. Surat-surat yang diturunkanya pun tidak sama jumlah panjang dan pendeknya, terkadang diturunkan sekaligus secara penuh dan terkadang sebagianya saja. Melalui kajian pustaka, Artikel menyimpulkan bahwa diturunkanya al-Qur’an secara berangsur-angsur banyak hikmah yang akan diperoleh yaitu menetapkan hati Rasulullah, melemahkan lawan-lawannya, mudah difahami dan dihafal, penyusunannya akan sesuai dengan lalulintas peristiwa atau kejadian. Penuruan ayat al-Qur’an secara beransur memberikan beberapa hikmah diantaranya: menguatkan hati Nabi Muhammad Saw; Mudah dihafal dan dipahami; orang-orang mukmin antusias dalam menerima Qur’an dan giat mengamalkannya; Mengiringi kejadian-kejadian di masyarakat dan bertahap dalam menetapkan suatu hukum; melemahkan lawan-lawannya (mukjizat), dan menantang orang-orang kafir yang mengingkari al-Qur’an.